Placental Gene Transcript Proportions are Altered in the Presence of In Utero Arsenic and Cadmium Exposures, Genetic Variants, and Birth Weight Differences - Deyssenroth, Maya A.; Peng, Shouneng; Hao, Ke; Marsit, Carmen J.; Chen, Jia (Frontiers in Genetics, 2022)
Background: In utero arsenic and cadmium exposures are linked with reduced birth weight as well as alterations in placental molecular features. However, studies thus far have focused on summarizing transcriptional activity at the gene level and do not capture transcript specification, an important resource during fetal development to enable adaptive responses to the rapidly changing in utero physiological conditions. In this study, we conducted a genome-wide analysis of the placental transcriptome to evaluate the role of differential transcript usage (DTU) as a potential marker of in utero arsenic and cadmium exposure and fetal growth restriction. Methods: Transcriptome-wide RNA sequencing was performed in placenta samples from the Rhode Island Child Health Study (RICHS, n=199). Arsenic and cadmium levels were measured in maternal toenails using ICP-MS. Differential transcript usage (DTU) contrasting small (SGA) and appropriate (AGA) for gestational age infants as well as above vs. below median exposure to arsenic and cadmium were assessed using the DRIMSeq R package. Genetic variants that influence transcript usage were determined using the sQTLseeker R package. Results: We identified 82 genes demonstrating DTU in association with SGA status at an FDR < 0.05. Among these, one gene, ORMDL1, also demonstrated DTU in association with arsenic exposure, and fifteen genes (CSNK1E, GBA, LAMTOR4, MORF4L1, PIGO, PSG1, PSG3, PTMA, RBMS1, SLC38A2, SMAD4, SPCS2, TUBA1B, UBE2A, YIPF5) demonstrated DTU in association with cadmium exposure. In addition to cadmium exposure and SGA status, proportions of the LAMTOR4 transcript ENST00000474141.5 also differed by genetic variants (rs10231604, rs12878, and rs373659), suggesting a pathway by which an in utero exposure and genetic variants converge to impact fetal growth through perturbations of placental processes. Discussion: We report the first genome-wide characterization of placental transcript usage and associations with intrauterine metal exposure and fetal growth restriction. These results highlight the utility of interrogating the transcriptome at finer-scale transcript-level resolution to identify novel placental biomarkers of exposure-induced outcomes.